(untitled) (Forum Penelitian Agro Ekonomi, 2016)
English The objective the paper is to elaborate some aspects those related to wetland conversion in Java. Although the wetland conversion data are various, it is predicted that not less than 40,000 ha per year of wetland in Java are converted to non agricultural uses. This phenomenon could threaten food security because Java is well known as the main rice producing area in Indonesia. This study shows that Java still contributes significantly to national rice production, i.e., on average more than 50 percent per year. Nevertheless, the long term wetland conversion can create a serious problem, especially in the matter of rice self sufficiency, if it is not well managed immediately. To anticipate the effects of wetland conversion, the government has implemented an area extensification program on wetland outside Java. Furthermore, the government has released many rules to protect agricultural land in Java from conversion to non agricultural uses. However, implementation those rules are not effective. Indonesian Makalah ini bertujuan melihat beberapa aspek yang berkaitan dengan alih fungsi lahan sawah di Pulau Jawa. Terjadinya alih fungsi lahan dikhawatirkan dapat mengganggu produksi pangan di Indonesia, karena selama ini Pulau Jawa menjadi andalan dalam produksi beras nasional. Diperkirakan tidak kurang dari 40.000 ha per tahun lahan sawah terkonversi ke penggunaan non sawah. Hasil studi menunjukkan bahwa Pulau Jawa masih tetap menjadi lumbung padi nasional, terbukti dari kontribusinya yang selalu lebih besar dari 50 persen. Namun, dalam jangka panjang konversi lahan sawah di Pulau Jawa dapat mengancam kecukupan pangan di Indonesia. Untuk mengantisipasinya pemerintah telah mengambil langkah dengan program pencetakan lahan sawah di luar Jawa. Di samping itu juga telah diterbitkan berbagai peraturan/perundang-undangan untuk melindungi lahan pertanian, walaupun implementasinya belum berjalan dengan efektif.